Tots! : 50 tot-ally awesome recipes from totchos to sweet po-tot-o pie - Whalen, Dan (Workman Publishing, 2018)
"It's a fact: Americans love tots, and last year consumed 3.5 billion of them. And not just at home. From fast-food joints to high-end restaurants, chefs are joining the tot trend, serving exotically spiced tots or fun mash-ups like Totchos, with tots replacing the corn chips in nachos. But now, prepare for TOT-al domination! Created by mad-genius food blogger Dan Whalen, Tots! elevates the friendly little tater to its place in the culinary spotlight. This irresistible cookbook with a nubby tot-texture on the cover offers 50 delicious, playful, and surprising recipes for snacks, appetizers, inspired main dishes, and inspired sides, even desserts. (Yes, you could create an entire tot-centric dinner.) Here are party dishes like Buffalo Tots and Tot Poutine. A Tot Caesar for an elegant starter. Tots for breakfast, like Tots Benedict and a Tot Shakshuka, and tots for dinner--Moules Tots, Chicken Tot Pie, Tater Tot Pizza, and Bibimtot. Side dishes--next Thanksgiving, try Sausage and Tot Stuffing. And for sweets lovers, Tot Churros (deep-fried and dipped in chocolate ganache), Apple Tot Crumble (that crispy salty tot topping really plays off the warm sweet apples), and Tot S'mores--a heavenly melt of a dish. Every recipe uses frozen commercial tots--but Dan Whalen also shows die-hard tot lovers how to make tots from scratch and then alter their creations with different spices (think Tots Vindaloo) and sauces. It's TOT-ally awesome"--